What does the European Union do? - Alesina, Alberto 1957-2020; Angeloni, Ignazio 1953-; Schuknecht, Ludger 1962- (NBER working paper series, 2001)
We construct a set of indicators to measure the policy-making role of the European Union (European Council, Parliament, Commission, Court of Justice, etc.), in a selected number of policy domains. Our goal is to examine the division of prerogatives between European institutions and national ones, in light of the implications of normative models and in relation to the preferences of European citizens. Our data confirm that the extent and the intensity of policy-making by the ED have increased sharply over the last 30 years. Such increase has taken place, at different speeds, and to different degrees, across policy domains. In recent times the areas that have expanded most are the most remote from the EEC's original mission of establishing a free market zone with common external trade policy. We conjecture that the resulting allocation may be partly inconsistent with normative criteria concerning the assignment of policies at different government levels, as laid out in the theoretical literature.